Preparation of sea buckthorn (Hippophae rhamnoides L.) seed meal peptide by mixed fermentation and its effect on volatile compounds and hypoglycemia - Yang, Jiangyong; Hong, Jingyang; Aihaiti, Aihemaitijiang; Mu, Ying; Yin, Xuefeng; Zhang, Minwei; Liu, Xiaolu; Wang, Liang (Frontiers in Nutrition, 2024)
This study employed mixed bacterial strains to ferment seabuckthorn seed meal into peptides, and conducted a comprehensive evaluation of the growth adaptive conditions, molecular weight distribution, volatile compounds, and in vitro hypoglycemic activity required for fermentation. Results showed that when the amount of maltose was 1.1% and MgSO4·7H2O was added at 0.15 g/L, the peptide yield reached 43.85% with a mixed fermentation of Lactobacillus fermentum, Bacillus subtilis, Lactobacillus casei, Lactobacillus rhamnosus, and Lactobacillus acidophilus. Components with a molecular weight below 1 kDa were found to be more effective in inhibiting the activity of α-amylase and α-glucosidase, with the identified sequence being FYLPKM. Finally, SPME/GC–MS results showed that 86 volatile components were detected during the fermentation of seabuckthorn seed meal, including 22 alcohols, 9 acids, 7 ketones, 14 alkanes, 20 esters, and 14 other compounds. With prolonged fermentation time, the content of acids and esters increased significantly.